(3fgL GdHdGZIs - (3Ydj Hf CHj WGdH,J (B40 (3g` s ((3Ydj Hf CHj GdbGSe Hf Ydj GdMGL s)
(3ChdgG (B:s
(3CeG HYO GdMeO ddg GdPj LYd GdMeO KefkG dfYeGFg, heYGPG ef HdGFg aEfj cfJ aj YfahGf GdSf s
(3BNQgG (B:s
(3hcdGege cdGe GdCHQGQ, YeGQ Gddjd hefGQ GdfgGQ, eJeSchf HMHd Gddg GdbQBfhCLSGOge aj GdYed Je GdLRA GdChd ef cJGH fgL GdHdGZI s
(3fSNI KGefIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa jSjQ aj HYV GdCdaGXs
(3hgj eYGQVI HGdCUds
(3hHjf SWhQgG hghGeTgG eYGmf hTQhM HChQGbgG WeS s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
Keywords: (3GdCOHs